Φρόνησις и медицинската етика - Поповска, Јасмина (Филозофски факултет, Скопје, 2019)
With the increasing influence of virtue ethics in the professional ethics (law, social work, business and management, education, medical care, medicine) φρόνησις is becoming key aspect in conceptualizing these ethical systems. The wider neoaristotelian interpretation of φρόνησις, leaves space φρόνησις to be defined as intellectual disposition for wisely conduct of moral virtues in light of particular cases. That allows φρόνησις to bring new reading of the concepts of moral clinical deliberation. Although Aristotle speaks of medicine in terms of τέχνη, and not of φρόνησις, the both perspectives of considering general principles and the specificity of particular cases that φρόνησις has, fits perfectly in practitioners’ needs faced with rigorous rules and codes or abstract deontological principles. In this article the concept of φρόνησις in medical ethics will be examined through two aspects of the medical-ethical discourse: the narrative understanding of the illness and medical-ethical reasoning. Considering the theoretical and the practical fruitfulness of φρόνησις in the clinical context, this text will question, the so-called, Aristotelian exegetical approach towards φρόνησις in contemporary ethics.
Keywords: φρόνησις, medical ethics, narrative understanding